Pengaruh Perkembangan Sastra Arab Pada Era 5.0 - Adelia Finanti (An-Nahdah Al-'Arabiyah)
The emergence of the 5.0 era which began in Japan in 2019 has had a major impact on the world of literature. The development of digital-based technology has disrupted the flow of social interactions in the real world, and social interactions now only occur digitally. Social and humanitarian matters have moved to the virtual world. Research This was done to obtain straightforward information brought in by the 5.0 era. The writing was carried out to influence Arabic literature in the 5.0 era, the type of research used was literature review. In the 5.0 era, Arabic literature can influence the field of technology and innovation by stimulating creative thinking and new discoveries. Inspirational literary works can stimulate the development of new technology or encourage innovative thinking in industry. The development of Arabic literature can be a source of inspiration and knowledge for future generations. Literary works that are rich in cultural, historical and philosophical values ​​can influence the formation and development of science. Plays an important role in preserving and developing the culture and identity of the Arab nation. Arabic Literature 5.0 reflects the development of identity and social change in the Arab world. These works discuss political, social and cultural changes and provide an opportunity for writers to think about social change.